Agency costs, risk shocks and international cycles - Marc-André Letendre; Joel Wagner (Bank of Canada, 2016)
We add agency costs as in Carlstrom and Fuerst (1997) into a two-country, two-good international business-cycle model. In our model, changes in the relative price of investment arise endogenously. Despite the fact that technology shocks are uncorrelated across countries, the relative price of investment is positively correlated across countries in our model, much as it is in detrended U.S./euro area data. We also find that the financial frictions tend to increase the volatility of the terms of trade and the international correlations of consumption, hours worked, output and investment. We then compare this model to an alternative model that also includes risk shocks à la Christiano, Motto and Rostango (2014). We use credit spread data (for the United States) to calibrate the AR(1) process for risk shocks. We find that risk shocks are too small to significantly impact the model's dynamics.
Keywords: E22; E32; E44; F44; 330; Business fluctuations and cycles; International topics